2021
DOI: 10.1038/s41401-021-00732-2
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of SARS-CoV-2-E channel inhibitors as antiviral candidates

Abstract: Lack of efficiency has been a major problem shared by all currently developed anti-SARS-CoV-2 therapies. Our previous study shows that SARS-CoV-2 structural envelope (2-E) protein forms a type of cation channel, and heterogeneously expression of 2-E channels causes host cell death. In this study we developed a cell-based high throughput screening (HTS) assay and used it to discover inhibitors against 2-E channels. Among 4376 compounds tested, 34 hits with cell protection activity were found. Followed by an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Cranberry extracts are well known for their pharmacological potential [ 42 , 43 , 44 , 45 ]. Furthermore, the natural product proanthocyanidins present in the cranberry extracts are widely used as cosmetic, suggesting a potential use as disinfectant for external use [ 46 ]. Su et al showed the antiviral activity of the cranberry juice and PACs against different virus, including human enteric virus surrogates, murine norovirus, feline calicivirus, bacteriophage MS2 (ssRNA), and bacteriophage phiX-174 (ssDNA) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cranberry extracts are well known for their pharmacological potential [ 42 , 43 , 44 , 45 ]. Furthermore, the natural product proanthocyanidins present in the cranberry extracts are widely used as cosmetic, suggesting a potential use as disinfectant for external use [ 46 ]. Su et al showed the antiviral activity of the cranberry juice and PACs against different virus, including human enteric virus surrogates, murine norovirus, feline calicivirus, bacteriophage MS2 (ssRNA), and bacteriophage phiX-174 (ssDNA) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PACs could act by binding and destroying the viral capsid structure or could cause inhibition of key enzymes involved in viral replication [ 49 ]. A recent study on the discovery of SARS-CoV-2 channel inhibitors as antiviral candidates, has shown that PACs directly bound to 2-E channel with binding affinity (KD) of 22.14 μM in surface plasmon resonance assay [ 46 ]. In addition, some studies have shown that PACs exposure prevents some bacteriophages from attaching to their bacterial host [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glycyrrhizin, Glycyrrhetinic acid, and Baicalin have also shown binding to E-channel protein. Proanthocyanidins have been reported to inhibit the MPro and E-channel protein of the SARS-CoV-2 [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, apigenin, baicalin, luteolin, hesperidin, genistein, proanthocyanidin and eriodictyol have been found to be capable of alleviating oxidative stress in diabetic nephropathy [63]. Incidentally, all the above flavonoid compounds have been reported to bind to SARS-CoV-2 protein components or the receptor hACE2 [54][55][56][64][65][66][67][68][69]. These flavonoids are also antioxidants suggesting a common mode of action in both COVID-19 and diabetes, which in all probability is through reducing oxidative stress.…”
Section: Synergistic Kidney Damage and Morbidity Due To Covid-19 And ...mentioning
confidence: 99%